1984
DOI: 10.1111/j.1095-8312.1984.tb01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional cranial analysis of large animalivorous bats (Microchiroptera)

Abstract: Large animalivorous bats include carnivorous, piscivorous and insectivorous microchiropterans. Skull proportions and tooth morphology are examined and interpreted functionally. Four widefaced bats from four families are convergent in having wide skulls, large masseter muscle volumes and stout jaws, indicating a powerful bite. Three of the four also have long canine teeth relative to their maxillary toothrows. Carnivorous bats have more elongate skulls, larger brain volumes and larger pinnae. The wide-faced bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
116
1
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 31 publications
1
116
1
3
Order By: Relevance
“…As in Freeman (1984Freeman ( , 1988 we used the sum of the natural logs of length, width, and height of head to cslinlatc head volume and thus, size of bat. Natural logs of all but one (angle of pinna) facial measurements were regressed against this cotnposite size character (SIZE) to determine whether facial measurements were correlated.…”
Section: Oralmentioning
confidence: 99%
See 3 more Smart Citations
“…As in Freeman (1984Freeman ( , 1988 we used the sum of the natural logs of length, width, and height of head to cslinlatc head volume and thus, size of bat. Natural logs of all but one (angle of pinna) facial measurements were regressed against this cotnposite size character (SIZE) to determine whether facial measurements were correlated.…”
Section: Oralmentioning
confidence: 99%
“…(1993) found no significant correlations between pinnal measurements and echolocation paraineters across families. Obligatory carnivorous bats, all nasal emitters, were found to have larger ear areas than oral emitting animalivorous bats (Freeman, 1984). Henson (1970), after reviewing several studies on the role of the pinnae in bats, concluded that the pinnae's main f~lnction was to increase the directionality of the sound reception system.…”
Section: Oralmentioning
confidence: 99%
See 2 more Smart Citations
“…This scarcity of studies on postcranial elements is surprising because bats are considered as a model for the study of the anatomy for the great diversification in their trophic niches, which has led to the development of many investigations about variations in the shape of the skull, mandible and teeth, particularly with regard to the type of food they consume (e.g. Freeman 1981Freeman , 1984Freeman , 1988Freeman , 1995Freeman , 1998.…”
Section: Introductionmentioning
confidence: 99%